A Chinese Herbal Formula, Gengnianchun, Ameliorates β-Amyloid Peptide Toxicity in a Caenorhabditis elegans Model of Alzheimer's Disease. (11th October 2017) - Meng, Fanhui; Li, Jun; Rao, Yanqiu; Wang, Wenjun; Fu, Yan
Abstract : Alzheimer's disease (AD) is an age-related neurodegenerative disorder, and the few drugs that are currently available only treat the symptoms. Traditional medicine or phytotherapy has been shown to protect against AD. In our previous studies, Gengnianchun (GNC), a traditional Chinese medicine formula with a prolongevity effect, protected against A β -induced cytotoxicity in pheochromocytoma cells (PC-12 cells) and hippocampal cells. Here, we investigated the effects and possible mechanisms by which GNC protected against A β toxicity using transgenic Caenorhabditis elegans CL4176. Our results showed that GNC effectively delayed the A β toxicity-triggered body paralysis of CL4176 worms. GNC decreased A β by reducing A β mRNA levels. Moreover, GNC significantly reduced reactive oxygen species in the AD model worms compared with the controls. In addition, GNC upregulated the daf-16, sod-3, hsp-16.2 genes, and enhanced DAF-16 translocation from the cytoplasm to the nuclei under oxidative stress conditions. GNC treatment of C. elegans strains lacking DAF-16 did not affect the paralysis phenotype. Taken together, these findings suggest that GNC could protect against A β -induced toxicity via the DAF-16 pathway in C. elegans . Further studies are required to analyze its effectiveness in more complex animals.